Strategi Manajemen Pendidikan Keberlanjutan Pada Pendidikan Vokasional - Suriagiri Suriagiri; Moh. Iqbal Assyauqi (Sekolah Tinggi Agama Islam Al Washiliyah Barabai, 2023)
Vocational education produces work-ready graduates who have skills according to the needs of the world of work. In the era of the Industrial Revolution 4.0, there were massive changes in various industries and the needs and abilities of workers. The Religious Education course is one of the Personality Development Courses (MPK). Based on the 2006 Director General of Higher Education Decree, every university can develop MPK signs according to their respective characteristics. The method used in this research is a literature study. The vocational curriculum needs to apply blended learning, which integrates face-to-face and online learning, to build graduates' abilities and skills more effectively. The curriculum must also include mastery of 4.0 competencies such as data, technological, and human literacy. For the vocational education curriculum to have a broad impact, the government, educational institutions, and industry must work together to revitalize the approach and content of the vocational education curriculum. Teachers must also be able to organize good learning to produce optimal graduate performance.